Electric field analysis of 66 kV and 110 kV SiR insulators under combined AC-DC voltages - ORAL, BÜLENT; İSPİRLİ, MEHMET MURAT (ELSEVIER, 2022)
Insulators are the most crucial part of power systems. The insulation performance of insulators is vital for the sustainability of power systems. Recently, silicone rubber (SiR) insulators are used frequently in all sections of the power systems. In this paper, a SiR insulator currently used in power transmission systems has been analyzed under combined AC-DC voltage using the finite element method. In the analysis, positive and negative DC voltages in different amplitude ratios were superimposed over the phase-earth operating voltage of the insulator. Analyses in the study were made in time-dependent. Only DC voltage was applied to the insulator for the first 60 s, AC + DC voltage was applied between 60 to 120 s. Thus, the electric field behavior of the SiR insulator under combined AC-DC voltage has been obtained. The change of electric field based on positive and negative DC components was investigated. As a result of the study, the effect of the polarity of the DC component in the combined voltage was observed. As a result, effect of the polarity of the DC component in the combined voltage on the maximum electric field intensity was observed. (C) 2021 The Author(s). Published by Elsevier Ltd.
Keywords: Composite voltage; Combined voltage; Finite element analysis; SiR insulators; COMPOSITE INSULATOR; PARTIAL DISCHARGE; SIMULATION